2000
DOI: 10.1097/00001756-200009110-00004
|View full text |Cite
|
Sign up to set email alerts
|

Visually induced activity in human frontal motor areas during simple visuomotor performance

Abstract: Visuomotor tasks elicit neuronal activity in primate motor areas at relatively short latencies. Although this early activity embodies features of visual responses (short latency, stimulusdependency), its sensory nature has been questioned. We investigated neural correlates of visuomotor performance in human motor areas using scalp and intracranial event-related potential measures. A simple visuomanual reaction-time task evoked early potentials at 133±145 ms post-stimulus which occurred much earlier than the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Although it might be expected that somatosensory processing would begin only after movement onset, recent studies have demonstrated that somatosensory processing can precede motor processing for a visuomotor task [Thut et al, 2000], either anticipating the to-be-received proprioceptive signal (efference copy) or using current body posture to model the to-beexecuted movement [Parsons et al, 1995]. As shown in Figure 2, primary somatosensory (S1) cortex activation (0 -100 msec) precedes M1 activation, and continued during M1 activation (100 -200 msec), but reached maximum after M1 activation (200 -300 msec).…”
Section: Resultsmentioning
confidence: 99%
“…Although it might be expected that somatosensory processing would begin only after movement onset, recent studies have demonstrated that somatosensory processing can precede motor processing for a visuomotor task [Thut et al, 2000], either anticipating the to-be-received proprioceptive signal (efference copy) or using current body posture to model the to-beexecuted movement [Parsons et al, 1995]. As shown in Figure 2, primary somatosensory (S1) cortex activation (0 -100 msec) precedes M1 activation, and continued during M1 activation (100 -200 msec), but reached maximum after M1 activation (200 -300 msec).…”
Section: Resultsmentioning
confidence: 99%
“…Times for stimuli presentation and TMS were chosen in order to explore the early cortical elaboration before the response generation. Previous EEG (Thut et al, 2000) and TMS singlepulse studies (Hoshiyama et al, 1997;Leocani, Cohen, Wassermann, Ikoma, & Hallett, 2000) employing visuo-motor tasks have shown the activation of the PMC-motor cortices 100Á200 ms after stimulus perception. Other studies employing go/no-go paradigms have shown the modulation of MEPs in the interval between Subjects were requested to press (go) or not to press (no-go) the space-bar of a PC keyboard on the basis of the colors presented on the pictures.…”
Section: Methodsmentioning
confidence: 95%
“…ELECTRA provides estimates of the 3D distribution of LFPs within the whole brain, which facilitates its direct comparison with recordings from intracranial electrodes. The advantages and limitations of ELEC-TRA have been explored using simulations [Grave de Peralta Menendez et al, 2000], comparisons with intracranial recordings in a task similar to the one reported here [Thut et al, 2000], and localization of epileptic activity [Michel et al, 1999]. These studies have shown that a scale-independent waveshape analysis circumvents one basic limitation of distributed inverse solutions, i.e., the uncertainty estimating source amplitudes [Grave de Peralta Menendez and Gonzalez Andino, 1998].…”
Section: Discussionmentioning
confidence: 99%